1993
DOI: 10.1071/rd9930459
|View full text |Cite
|
Sign up to set email alerts
|

A model for follicle selection and the determination of ovulation rate in the ewe

Abstract: A model for folliculogenesis is proposed that is based as far as possible on a knowledge of physiological, rather than anatomical, changes taking place during follicle development. The model is therefore functional, rather than descriptive, and consists of five classes of follicles that have been defined by their dependency and sensitivity to gonadotrophins. These classes are: primordial, committed, gonadotrophin-responsive, gonadotrophin-dependent and ovulatory. The model is an attempt to encourage discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
7

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 33 publications
2
115
0
7
Order By: Relevance
“…Other studies, however, reported lower numbers of preantral follicles in goat [4] and sheep [20] ovaries. It is well-known that besides the species differences, preantral follicle populations may be affected by factors such as breed [16], age [18,21], hormone levels and reproductive stage [22], and nutrition [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, reported lower numbers of preantral follicles in goat [4] and sheep [20] ovaries. It is well-known that besides the species differences, preantral follicle populations may be affected by factors such as breed [16], age [18,21], hormone levels and reproductive stage [22], and nutrition [23].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro evidence suggests that, although appreciable amounts of estradiol are detected in follicles of > 0.5 mm diameter, small antral follicles respond individually and not identically to gonadotrophins indicating a hierarchical development [31]. In sheep, the ability to progress to meiotic cycle and gain the ability to develop up to the blastocyst stage is achieved progressively as follicle diameter increases [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…These data are in accordance with many other authors (Jewgenow and Göritz, 1995;Jewgenow and Stolte, 1996;Amorim et al, 1998;Rodrigues et al, 1998). A variety of factors has been described which may affect ovarian follicular populations, including age (Peters, 1976), breed (Cahill et al, 1979;Driancourt et al, 1985), reproductive stage (Erickson et al, 1976), nutrition (Scaramuzzi et al, 1993) and genetic factors (Erickson, 1966aErickson, 1966bCahill et al, 1979).…”
Section: Discussionmentioning
confidence: 99%